A novel gold nanosol SERS quantitative analysis method for trace Na+ based on carbon dot catalysis. (15th August 2019) - Li, Chongning; Wang, Haidong; Luo, Yanghe; Wen, Guiqing; Jiang, Zhiliang
Highlights: CDCa exhibited strong catalysis of nanogold reaction between HAuCl4 and H2 O2 . PA binds with CDCa to inhibit its nanocatalysis. The intensity of the SERS peak at 1615 cm −1 is increased linearly with Na + concentration increasing. The SERS quantitative analysis method for Na + has high sensitivity. Abstract: The Ca-doped carbon dots (CDCa ) exhibited strong catalysis of HAuCl4 -H2 O2 reaction to produce gold nanoparticle (AuNP), using Vitoria blue 4R (VB4r) as molecular probe, it appeared a strong surface enhanced Raman scattering (SERS) peak at 1615 cm −1 in the AuNP nanosol substrate. When catalyst CDCa increased, the SERS peak enhanced linearly owing to AuNPs increasing, that is, the AuNP concentration is linear to SERS signal. Potassium pyroantimonate (PA) ligand can adsorb on CDCa surface to inhibit the catalysis and cause the SERS peak decreasing. The analyte of Na + reacts with PA to produce the stable precipitate of [Na2 (PA)] and free CDCa catalyst. The more Na +, the more CDCa released, and the stronger SERS signal due to more AuNP substrate. Accordingly, a SERS quantitative analysis method for Na + was developed based on CDCa catalytic SERS reaction, with a linear range of 0.004–0.043 μmol/L, and a detection limit of 0.0019 μmol/L Na.